Prevalence and determinants of language impairment in non‐demented amyotrophic lateral sclerosis patients. (11th December 2022) - Solca, Federica; Aiello, Edoardo Nicolò; Torre, Silvia; Carelli, Laura; Ferrucci, Roberta; Verde, Federico; Ticozzi, Nicola; Silani, Vincenzo; Monti, Alessia; Poletti, Barbara
Abstract: Background and purpose: This study aimed at estimating the prevalence of language impairment (LI) in a large, clinic‐based cohort of non‐demented amyotrophic lateral sclerosis (ALS) patients and assessing its underpinnings at motor and non‐motor levels. Methods: Non‐demented ALS patients ( N  = 348) underwent the Edinburgh Cognitive and Behavioural ALS Screen (ECAS), as well as an assessment of behavioural/psychiatric and motor‐functional features. The prevalence of LI was estimated based on the proportion of patients showing a performance below the age‐ and education‐adjusted cut‐off on the ECAS‐Language. Multiple regression models were run to assess the determinants of language functioning and impairment. Results: The prevalence of LI was 22.7%. 46.6% of the variance of ECAS‐Language scores remained unexplained, with only the ECAS‐Executive positively predicting them ( p  < 0.001; η 2  = 0.07). Similarly, only a lower score on the ECAS‐Executive predicted a higher probability of a below cut‐off ECAS‐Language performance ( p  < 0.001). Spelling and Naming tasks were the major drivers of ECAS‐Language performance. Conclusions: This study suggests that, in non‐demented ALS patients, LI occurs in ≈23% of cases, is significantly driven by executive dysfunction but, at the same time, partially independent of it and is not associated with other motor or non‐motor features.